PENGUATAN PUTUSAN BAWASLU KABUPATEN/KOTA MENJADI FINAL DAN MENGIKAT DALAM SENGKETA PEMILIHAN DENGAN PERSPEKTIF KEPASTIAN HUKUM - Batara Abdullah Nasution; Zulkifli AR (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
The decision of the Regency/City Bawaslu is deemed not strong enough to provide legal certainty in the Regional Election system. For this reason, it is necessary to create legal certainty in resolving disputes over the Regional Election process by strengthening the decisions of Regency/City Bawaslu. This research is a normative legal research. The results of the study indicate that the decision of the Regency/City Bawaslu needs to be strengthened against the nature of the decision to be final and binding which aims to create legal certainty in the Regional Election. Keywords: Decision, Regional Election, dispute, final and binding